Density of Macroalgae Species on Pasir Panjang Beach Kupang City - Yusnaeni; Valentina Begang (Universitas Tidar, 2023)
Density of Macroalgae Species on Pasir Panjang Beach, Kupang City Macroalgae have an important role for productivity and protection for other marine biota, namely as primary producers, carbon sinks, cosmetic ingredients and have economic value in the trade sector. Pasir Panjang Beach has a high aesthetic value, so it is used as a recreational space for the city community and as a destination for the development of tourist attractions. This study aims to determine the types and density of macroalgae in Pasir Panjang Beach, Kupang City. This study uses the line transect method with quadrant sampling technique with a size of 1m x 1m. The sample consisted of 100 plots of 10 transects at 2 stations. The samples were analyzed quantitatively descriptively to determine the morphological characteristics of the species and the density analysis of each species. The results found 15 types of macroalgae were divided into 3 divisions, namely the Chlorophyta division (7 species), Rhodophyta division (6 species, and Phaeophyta division (2 species). The highest species density at station 1 was Hypnea sp (33.38 ind/m2) and the lowest namely the species Acantopora spicifera (0.02 ind/m2), while at station 2, the highest density was Gracilaria salicornia (6.06 ind/m2) and the lowest density was Neomeris dumentosa (0.14 ind/m2). The conclusions are 1) There are 15 types of macroalgae from 3 divisions namely Chlorophyta, Rhodophyta and Phaeophyta, 2) The species density differs between stations.